Anion-conductive membranes based on 2-mesityl-benzimidazolium functionalised poly(2, 6-dimethyl-1, 4-phenylene oxide) and their use in alkaline water electrolysis. (6th June 2018) - Marinkas, Angela; Struźyńska-Piron, Izabela; Lee, Yona; Lim, Ahyoun; Park, Hyun S.; Jang, Jong Hyun; Kim, Hyoung-Juhn; Kim, Jihyun; Maljusch, Artjom; Conradi, Oliver; Henkensmeier, Dirk
Abstract: For development of anion exchange membrane (AEM) water electrolysis systems, a series of polymers was synthesised by reacting 2-mesityl-benzimidazole (BIM) and brominated poly-(2, 6-dimethyl-1, 4-phenylene oxide) (Br-PPO) in a Menshutkin reaction, and permethylating the attached BIM groups. The degree of bromination of Br-PPO can be easily monitored by IR spectroscopy: A correlation with the shift of the band around 1190 cm −1 was found. The IEC values of the prepared materials ranged between 1.6 and 2.9 mmol OH − g −1 . Only materials with an IEC value of 1.9 (PPO24-BIM) reproducibly formed self-supporting membranes. This may be related to the degree of crystallinity, which decreased from 14 to 3% when the IEC increased from 1.6 to 3 mmol OH − g −1 . Materials with IEC values of 1.6 and 2.2 can form self-supporting membranes, but not reproducibly. PPO24-BIM showed a conductivity of 8 mS cm -1 at room temperature, a thermal stability well above 200 °C, and mechanical properties similar to those of commercial FAA3-30 membranes. During water electrolysis, a current density of 300 mA cm -2 at 1.8 V was obtained. At 80 °C in 1 M KOH, degradation of BIM and the PPO backbone were observed by IR spectroscopy and monitoring conductivity and weight loss. Graphical abstract: Image 1 Highlights: 2-Mesityl-1-methyl-benzimidazolium (BIM) functionalised PPO membranes were prepared. Shift of IR band at 1190 cm −1 correlates with degree of bromination of PPO. Due to BIM's bulkiness and PPO's brittleness, only some ratios give stable membranes. Alkaline water electrolysis at 1.8 V gave a current density of 300 mA cm −2 . Water vapour permeability of several membranes was measured.